Study on the Constant Resistance Coupling Support Technology for Rock Column at the Intersection Point of Deep Soft Rock Large Section Roadway: A Case Study in China - Huichen Xu; Yong Zhang; Jinkun Yang; Jiangbing Li; Xiaoming Sun; Cheng Xie (Shock and Vibration)
In order to solve the problem on the serious deformation and failure of the rock column at the intersection of large cross sections in Shiyakou coal mine, based on field engineering geomechanics analysis, theoretical analysis, and three-dimensional numerical simulation, combined with the mutual coupling between the constant resistance coupling support cable and surrounding rock, a dual-control constant-resistance coupling control technology with high prestressed constant resistance coupling support cable as the core solution is proposed. The field engineering practice and field monitoring data show that the dual-control constant resistance coupling support control technology has a good control effect on the deformation of the rock column at the large cross section intersection of the deep soft rock roadway and can be effectively used in the engineering practice.